Evaluasi Penerapan TER PPh 21 Pada Pemungut Pajak Berdasarkan The Four Maxim - Alvidhea Melfianti; Yulianti Abbas (Owner : Riset dan Jurnal Akuntansi, 2025)
The complexity of Income Tax Article 21 calculations has led the Indonesian government, through the Directorate General of Taxes (DGT), to introduce a new calculation scheme known as the Average Effective Tax Rate (TER). This policy was designed to provide simplicity, convenience, and fairness. However, its implementation in practice has not been free from criticism. This study aims to evaluate the implementation of TER in the withholding of Income Tax Article 21 using Adam Smith’s Four Maxims: equity, certainty, convenience, and efficiency. A qualitative method was employed, with data collected through in-depth interviews with tax authorities, tax withholders, and tax consultant. The findings indicate that in terms of the justice principle, the ability-to-pay and horizontal equity principles are relatively fulfilled. However, the benefit principle is not universally perceived by all taxpayers, and vertical equity remains suboptimal—particularly for recipients of non-regular income. The principle of certainty has been fulfilled normatively, but challenges remain in the form of interpretational differences over certain provisions. The convenience principle is not yet fully achieved due to the instability of the DGT system and ongoing technical difficulties. Lastly, the efficiency principle has been optimally met, though the initial implementation incurred high financial cost.